A Framework for Online Experimenter-Moderated Looking-Time Studies Assessing Infants’ Linguistic Knowledge - Bacon, Desia; Weaver, Haley; Saffran, Jenny (Frontiers in Psychology, 2021)
Online data collection methods pose unique challenges and opportunities for infant researchers. Looking-time measures require relative timing precision to link eye-gaze behavior to stimulus presentation, particularly for tasks that require visual stimuli to be temporally linked to auditory stimuli, which may be disrupted when studies are delivered online. Concurrently, by widening potential geographic recruitment areas, online data collection may also provide an opportunity to diversify participant samples that are not possible given in-lab data collection. To date, there is limited information about these potential challenges and opportunities. In Study 1, twenty-one 23- to 26-month-olds participated in an experimenter-moderated looking-time paradigm that was administered via the video conferencing platform Zoom, attempting to recreate in-lab data collection using a looking-while-listening paradigm. Data collected virtually approximated results from in-lab samples of familiar word recognition, after minimal corrections to account for timing variability. We also found that the procedures were robust to a wide range of internet speeds, increasing the range of potential participants. However, despite the use of an online task, the participants in Study 1 were demographically unrepresentative, as typically observed with in-person studies in our geographic area. The potentially wider reach of online data collection methods presents an opportunity to recruit larger, more representative samples than those traditionally found in lab-based infant research, which is crucial for conducting generalizable human-subjects research. In Study 2, microtargeted Facebook advertisements for online studies were directed at two geographic locations that are comparable in population size but vary widely in demographic and socioeconomic factors. We successfully elicited sign-up responses from caregivers in neighborhoods that are far more diverse than the local University community in which we conduct our in-person studies. The current studies provide a framework for infancy researchers to conduct remote eye-gaze studies by identifying best practices for recruitment, design, and analysis. Moderated online data collection can provide considerable benefits to the diversification of infant research, with minimal impact on the timing precision and usability of the resultant data.